PENGARUH REWARD DAN KEMAMPUAN TERHADAP KINERJA DENGAN MOTIVASI INSTRINSIK SEBAGAI VARIABEL INTERVENING PADA HOTEL PANGERAN PEKANBARU - Sufriyadi, Ricko; Fathoni, Ahmad Fauzan; ', Marnis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Human resources is a factor that is planned, moving, and oversee all activities of the company. Given the importance of human resources, each company must have tried to get a qualified and productive employees to run the company. This study aims to analyze the performance of employees Pangeran Pekanbaru. In this penlitian used random sampling, the sampling technique and deliberately randomized study. Data were collected using a questionnaire method is to provide a list of questions or questionnaires directly to the respondents. The data analysis in this study using the classical assumption test and multiple linear regression through SPSS 20. The results showed that the performance of the variable reward positive effect with a coefficient of 0.493 and a positive effect on the variable performance capabilities with a coefficient of 0.269. Variable rewards on intrinsic motivation positively berpenaruh with variable coefficients of 0.510 and a positive effect on the ability of intrinsic motivation with a coefficient of 0.350. And on the other hand, the relationship between intrinsic motivation is also a positive effect on employee performance with a coefficient of 0.584. Employee performance can be increased along with the increase in the reward given by the company and the capabilities of employees, as well as intrinsic motivation.Keywords : Reward, Ability, Intrinsic Motivation, Performance